The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1088/0957-0233/20/1/015805
|View full text |Cite
|
Sign up to set email alerts
|

An optical coherence tomography (OCT)-based air jet indentation system for measuring the mechanical properties of soft tissues

Abstract: A novel noncontact indentation system with the combination of an air jet and optical coherence tomography (OCT) was presented in this paper for the quantitative measurement of the mechanical properties of soft tissues. The key idea of this method is to use a pressure-controlled air jet as an indenter to compress the soft tissue in a noncontact way and utilize the OCT signals to extract the deformation induced. This indentation system provides measurement and mapping of tissue elasticity for small specimens wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 61 publications
(90 reference statements)
1
69
0
Order By: Relevance
“…The air-jet system comprised a testing probe and a data collection segment [20]. The probe consisted of a 1 mm air-jet bubbler that contained a super luminescent diode light source (DenseLight, DL-CS3055 A, Singapore) operated at a central wavelength of 1310nm, a nominal -3 dB spectral bandwidth of 50nm, and a nominal output power of 5 mW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The air-jet system comprised a testing probe and a data collection segment [20]. The probe consisted of a 1 mm air-jet bubbler that contained a super luminescent diode light source (DenseLight, DL-CS3055 A, Singapore) operated at a central wavelength of 1310nm, a nominal -3 dB spectral bandwidth of 50nm, and a nominal output power of 5 mW.…”
Section: Methodsmentioning
confidence: 99%
“…An optical coherence tomography (OCT)-based air-jet indentation system is a novel noncontact method that has recently been developed for characterizing the biomechanical properties of soft tissues [20], The system utilizes the optical interferometric technique for capturing the depth that the tested tissue displaces during indentation, and a pressure controlled air-jet as an indenter for measuring the stiffness of the tissue. The force-depth curves can be derived from the indentation test, and the stiffness obtained represents the biomechanical properties of the whole tissue layer under the surface of the wound to be tested [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that further work should be conducted on how the smooth muscle cells highly present in the media layer are affected by PG polypropylene glycol immersion for a better understanding of these effects. inTrODUcTiOn Optical coherence tomography (OCT) is an imaging modality of micrometric scale permitting the visualization of tissue microstructure at different sub-surface levels (high-resolution and crosssectional images acquisition with a near-infrared light) (Yang et al, 2006;Huang et al, 2009;Real et al, 2013;Ling et al, 2016;Mahdian et al, 2016). It is continuously under development, with for instance recent real time acquisitions (Schmitt et al, 1994;Boppart et al, 1999;Yabushita et al, 2002;Yang et al, 2006;.…”
mentioning
confidence: 99%
“…For medical applications, this technique has been employed to detect and characterize the morphological alterations of microstructure and structure of human tissues undergoing pathologic changes such as: atherosclerotic plaques, thoracic aortic aneurysms, airways dysfunctions (asthma and bronchiectasis), gastrointestinal tumor tissue, articular cartilage degenerative changes, retinal vascular diseases, microfractures and inflammations in oral tissues, etc. It has also been used on biomaterials such as dental implants, three-dimensional (3D) porous scaffolds applied in tissue engineering and hydrogels, among others (Brezinski et al, 1996;Wang, 2002;Wang and Elder, 2002;Yabushita et al, 2002;Yang et al, 2006Yang et al, , 2007Huang et al, 2009;Prati et al, 2010;Williamson et al, 2011;Li et al, 2012;Real et al, 2013;Jia et al, 2015;Liba et al, 2016;Mahdian et al, 2016;Nebelung et al, 2016;Alibhai et al, 2017).…”
mentioning
confidence: 99%
“…Recent studies successfully combine the air puff function with more advanced spectral optical coherence tomography (sOCT) system. [6][7][8] However, due to the limitation of techniques, both the commercial ORA and the new sOCT can only obtain the dynamic corneal parameters at a certain point of the cornea.…”
Section: Introductionmentioning
confidence: 99%